The Paradigm of Tauhid And Educational Implications Morality of The 21st Century Generation - Muwaviyah Nihayatil ‘Ulum (Labor Program Studi Pendidikan Sosiologi, 2023)
The aim of this study is to establish a monotheistic paradigm amidst the moral degradation occurring in the current millennial era. This study is a qualitative research, using literature data related to Tauhid, and the like. The data analysis used is descriptive analysis. The results of this research indicate that the current millennial generation (21st century) is a generation full of challenges and innovations, marked by technological advancements that facilitate access to desired goals. This has led to significant moral degradation in this generation, caused by the lack of application of monotheism in life. The paradigm of monotheism can be built through socialization and spiritual reinforcement as a means of self-control against negative influences.